Importance-Performance Analysis: Evaluation E-Business Motivation Among SMEs in Indonesia - Kusmantini, Titik; Pratiwi, Krisnandini Wahyu; Gusaptono, Hendri; Haryanto, Darban (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study aims to fill a research gap, namely exploring the extent to which small companies in Indonesia, especially batik SMEs in the Bantul district. The aim of the research is to understand the adoption of e-business applications. Evaluation of the extent to which the motivation of companies to adopt an e-business strategy is carried out using Importance-Performance Analysis (IPA). A total of 122 SMEs were obtained and sampled using the criteria of SMEs as family businesses and have implemented electronic-based business applications such as marketing blogs or Instagram or Facebook. The analysis technique used is not only based on the IPA framework but also using a sample data sorting technique with a Cartesian diagram to obtain what items of expectation have motivated SMEs to adopt e-business and how the performance achievements of these expectations have been achieved. This study identifies the priority items for SMEs in maximizing the use of e-commerce to support online sales, selection of potential supplier sources, and efforts to save promotional budgets.